Perineural invasion on biopsy is associated with upstaging at radical prostatectomy in Gleason score 3 + 4 = 7 prostate cancer. Issue 11 (5th October 2016) - Flood, Trevor A.; Schieda, Nicola; Keefe, Daniel T.; Morash, Chris; Bateman, Justin; Mai, Kien T.; Belanger, Eric C.; Robertson, Susan J.; Breau, Rodney H.
Abstract : This study assesses if perineural invasion (PNI) detected on biopsy with Gleason score (GS) 3 + 4 = 7 prostate cancer (PCa) is associated with upstaging/upgrading of disease after radical prostatectomy (RP). 154 patients with GS 3 + 4 = 7 PCa diagnosed from biopsy who underwent RP were assessed for PNI. The percentage of biopsy sites with PNI (%PNI) was also calculated. Pattern 4 morphologies (ill‐defined glands [IDG], fused, cribriform, and glomerulations) were also assessed. Clinical information, GS and stage after RP were retrieved from the medical records. 45 % (69/154) of patients were upstaged (≥pT3) and 29 % (44/154) were upgraded to GS >3 + 4 = 7 after RP. 37 % (57/154) of patients had PNI which was associated with upstaging (RR 1.4; P = 0.04) but not upgrading (RR 0.9; P = 0.7). There was higher %PNI in upstaged patients (12.1 % ± 1.8 vs. 7.1 % ± 1.5, P = 0.03) with a significant correlation between %PNI and ≥pT3 ( r = 0.178, P = 0.027). After multivariate analysis, only cribriform formations were significantly associated with upstaging ( P = 0.009). The presence of PNI in biopsies with GS 3 + 4 = 7 PCa is associated with upstaging at RP but is a weaker predictor of ≥pT3 disease than cribriform morphology.